2017
DOI: 10.1016/j.cherd.2016.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Studying model suspensions using high resolution synchrotron X-ray microtomography

Abstract: Please note that changes made in the online proofing system will be added to the article before publication but are not reflected in this PDF.We also ask that this file not be used for submitting corrections. ARTICLE IN PRESSCHERD 2506 1-17 chemical engineering research and design x x x ( 2 0 1 6 ) xxx-xxx Contents lists available at ScienceDirectChemical Engineering Research and Design j o u r n a l h o m e p a g e : w w w . e l s e v i e r . c o m / l o c a t e / c h e r dStudying model suspensions using hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This was achieved using synchrotron microtomography to observe the interactions at high resolution and to monitor the dynamics of change. This work was a follow up of previous work conducted focusing on different volumes of the same secondary liquid (water) and the effect this has on the dynamics, as well as the importance of surface area to volume ratio in driving the mass transfer of sucrose from the bulk suspension [18].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This was achieved using synchrotron microtomography to observe the interactions at high resolution and to monitor the dynamics of change. This work was a follow up of previous work conducted focusing on different volumes of the same secondary liquid (water) and the effect this has on the dynamics, as well as the importance of surface area to volume ratio in driving the mass transfer of sucrose from the bulk suspension [18].…”
Section: Resultsmentioning
confidence: 96%
“…This technique enabled the evolution of the system to be monitored over a set period of time. Previous work has focused on studying the mass transfer and changes in dynamics when changing the volume of secondary liquid added [18,19]. This work will concentrate on changing the secondary liquid type (in particular the sucrose concentration), on the dynamics of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that pH strongly influences the gas diffusion between the bubbles of different milk proteins at different pHs. In another study, researchers tracked the 3D movement of a secondary immiscible liquid (water or saturated sucrose solution) when added to crystalline‐suspended sucrose in a continuous phase of sunflower oil (Islam et al., 2017). They concluded that the movement of droplets was due to the hydrophilicity and solubility of sucrose.…”
Section: Optical Techniques and How They Hold The Key To Filling The ...mentioning
confidence: 99%
“…As mentioned earlier, phase-contrast XCT is the preferred mode for studying low-density, multi-phasic systems such as food. By exploiting a synchrotron X-Ray source, details of the microstructures of oil/water emulsions (Nielsen et al, 2016), sucrose suspensions in oil (Hounslow et al, 2016) and ice-cream (Guo et al, 2017; samples have been obtained. All the major phases in these samples could be identified, allowing a better understanding of the spatial arrangement of all ingredients in the sample matrix.…”
Section: X-ray Tomographymentioning
confidence: 99%
“…In Hounslow et al, 2016, a model food system featuring a water droplet added to a suspension of sucrose particles in oil was studied with XCT, due to its ability to monitor simultaneously the motion of the droplet and the interactions and structural changes taking place during the experiment. The sample investigated in this work represents a model of how moisture diffusion can trigger phase transitions between fluid and pastelike material.…”
Section: X-ray Tomographymentioning
confidence: 99%